44.7k views
14 votes
Decide if the expression is positive or negative. Explain in words how you know, please.

-11 x (2/3) and -11 x (-2/3)

User Rubeonline
by
4.9k points

1 Answer

14 votes

Explanation:

The first expression is :


-11* (2)/(3)

Numerator = -11×2 = -22

Denominator = 3

So, answer will be :


-11* (2)/(3)=(-22)/(3) (negative)

The second expression is:


-11* (-2)/(3)

Numerator = -11×-2 = 22

Denominator = 3

So, the answer will be :


-11* (-2)/(3)=(22)/(3) (positive)

Hence, this is the required solution.

User StuR
by
5.2k points